Normal Functioning Fused Pelvic Kidney: A Very Rare Renal Anomaly (TAJ: Journal of Teachers Association, 2018)
This study highlights two cases having fused pelvic kidneys who were referred at this institute by clinicians/nephrologists for 99mTechnetium (99mTc) DMSA and DTPA renal scintigraphy. One case was 24 year old female and the other case was 21 year old male. Both cases were undergone ultrasonographic examination for correlative purpose before renal scintigraphy. Their urinary drainage system was assessed with DMSA and DTPA renal scintigraphy, showing normal functioning fused pelvic kidneys. The authors also used diuretic during DTPA renogram to exclude the true obstructive feature of urinary tract.TAJ 2016; 29(1): 55-57